2013
DOI: 10.1523/jneurosci.5885-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Glutamatergic Neurons Fails to Trigger a Neurogenic Response in the Adult Neocortex

Abstract: Adult neurogenesis is actively studied in part because of the potential to manipulate endogenous neural stem and progenitor cells for tissue repair. Although constitutive generation of neurons in the adult rodent olfactory bulb and hippocampal dentate gyrus is widely accepted and stroke-induced generation of striatal inhibitory neurons consistently observed, evidence supporting the generation of neurons in the neocortex after neuronal loss remains slim. Nevertheless, a few studies suggested that targeted apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…Consistent with previous report (Diaz et al, 2013), we observed that microglial reactions represent the earliest cellular response to DT-triggered apoptotic cell death.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous report (Diaz et al, 2013), we observed that microglial reactions represent the earliest cellular response to DT-triggered apoptotic cell death.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…This hypothesis has not been confirmed in other studies (Arvidsson et al, 2002;Shimada et al, 2010;Diaz et al, 2013). To address this issue, we labeled progenitor cells in SVZ at P3 by intraventricular injection of lentiviruses carrying GFP-expressing construct (Figs.…”
Section: Apoptotic Cell Death Does Not Induce Neuronal Recruitment Frmentioning
confidence: 86%
“…No clear evidence of spontaneous neurogenesis has been shown in the intact mouse (as opposed to rat) cerebral cortex, thus confirming the importance of the animal species in parenchymal neurogenesis (see Table 1) and the possible differences existing in cortical structural plasticity when comparing rats and mice. On the other hand, striking results have been obtained in the lesioned mouse cortex (Magavi et al 2000;Chen et al 2004), but this remains controversial and awaits validation (Diaz et al 2013).…”
Section: Parenchymal Neurogenesismentioning
confidence: 99%
“…However, this generation of new neurons in the postnatal/adult cortex seems to be dependent on unknown signals: those not usually elicited by most types of lesions (Saha et al, 2012;Diaz et al, 2013). It is also still unclear whether these new neurons could be derived from progenitor cells in the parenchyma itself (Palmer et al, 1999;Guo et al, 2010) or the marginal zone/layer 1 (Costa et al, 2007;Ohira et al, 2010).…”
Section: Environmental Signals and Neuronal Plasticity In The Developmentioning
confidence: 99%